Modelo de gestión para desarrollo de viviendas De interés social para el sindicato provincial de Chóferes profesionales de El Oro - Ochoa Romero, Edgar Patricio (2017)
The concept of management model as such is analyzed by several authors with varied theories in such a way that they present several similarities between them, with small variations that allow to have a broader range of what management model means. Rivera and Serrano (2013) decompose the concept for each of the components, establishing that model is a reference to an archetype susceptible to imitation, management to the effect of managing, determining together that management model is a frame of reference to manage.